PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBINA AKHLAK SISWA DI SMP NEGERI 2 TUREN - Ahmad Riza Nabil Asiqin; Azhar Haq; Dwi Fitri Wiyono (VICRATINA, 2021)
The role of Islamic religious education teachers in fostering student morals at SMP Negeri 2 Turen. The objectives of the teacher's role in fostering student morals at SMP Negeri 2 Turen are as follows: (1) To describe the role of Islamic religious education teachers in fostering student morals at SMP Negeri 2 Turen Malang. (2) To describe the supporting and inhibiting factors in the nature of Islamic religious education teachers in fostering the morals of students at SMP Negeri 2 Turen Malang. The results of the study are: (1) The form of the teacher's role in exemplary at SMP Negeri 2 Turen Malang has several forms that are applied, so that with the various forms of exemplary roles that are applied, students are able to apply moral attitudes, as applied by exemplary teachers, namely: providing guidance students, the existence of moral material, performing congregational prayer attendance, the existence of punishment, giving advice, and religious activities. (2) Supporting Factors, the role of Islamic education teachers in education, exemplary teachers, facilities for habituation activities, parental support. Inhibiting factors, while the factors that hinder the role of exemplary religious education teachers, namely students who lack discipline, are very difficult because there are some students who are indeed difficult to advise and underestimate the advice given by Islamic religious education teachers.